2014
DOI: 10.1177/0887403414526231
|View full text |Cite
|
Sign up to set email alerts
|

Police Sexual Misconduct

Abstract: Police sexual misconduct is often considered a hidden crime that routinely goes unreported. The current study provides empirical data on cases of sex-related police crime at law enforcement agencies across the United States. The study identifies and describes incidents where sworn law enforcement officers were arrested for one or more sex-related crimes through a quantitative content analysis of published newspaper articles and court records. The primary news information source was the Google News search engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…A related endeavor has been undertaken by policing scholar Phillip Stinson, who developed a system for harvesting news reports of police officers who have been arrested. These data have enabled him to study such diverse topics as police sexual misconduct (Stinson, Liederbach, Brewer, & Mathna, 2014), drunk driving (Stinson, Liederbach, Brewer, & Todak, 2013), drug-related corruption (Stinson, Liederbach, Brewer, Schmalzried, et al, 2013), and most recently, violence (Stinson, Brewer, & Bridges, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A related endeavor has been undertaken by policing scholar Phillip Stinson, who developed a system for harvesting news reports of police officers who have been arrested. These data have enabled him to study such diverse topics as police sexual misconduct (Stinson, Liederbach, Brewer, & Mathna, 2014), drunk driving (Stinson, Liederbach, Brewer, & Todak, 2013), drug-related corruption (Stinson, Liederbach, Brewer, Schmalzried, et al, 2013), and most recently, violence (Stinson, Brewer, & Bridges, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research focused on police crimes associated with sexual misconduct identified 548 cases within a three-year window including 118 cases of rape, indicating that these sorts of heinous police crimes occur with some regularity within jurisdictions across the nation. This research also found victims to be inordinately young, mostly children (Stinson et al 2014a(Stinson et al , 2014c. Other studies within this line of research focus on the most egregious forms of sex-related crime labeled as police sexual violence, including rape, sodomy, and aggravated sexual assault.…”
Section: Research On Police Crime and Victimizationmentioning
confidence: 66%
“…Decision tree techniques have received attention due to their ability to handle interaction effects in data without being bound to statistical assumptions (Sonquist, 1970). Classification tree analysis has been used to examine police practices including career-ending police misconduct (Kane & White, 2013), police drug corruption arrests (Stinson et al, 2013), fatal and nonfatal incidents involving conductive energy devices (White & Ready, 2009), police sexual misconduct (Stinson, Brewer, Mathna, Liederbach, & Englebrecht, 2014; Stinson, Liederbach, Brewer, & Mathna, 2014), and police drunk driving (Stinson, Liederbach, Brewer, & Todak, 2014). This study utilized the Classification and Regression Trees (CART) decision tree predictive analytic algorithm.…”
Section: Methodsmentioning
confidence: 99%